Recent Advances in Phytoconstituent-Based Alpha Glucosidase Inhibitors and Therapeutic Potential for Type 2 Diabetes Mellitus - Ali, Tarmeen; Mishra, Ganesh Prasad (Indian Journal of Pharmaceutical Education and Research, 2026)
Type 2 Diabetes Mellitus is a chronic metabolic disorder characterized by insulin resistance and impaired glucose metabolism. Alpha-glucosidase inhibitors have emerged as a promising therapeutic approach to managing postprandial hyperglycemia by delaying carbohydrate digestion and glucose absorption. Phytoconstituent-based Alpha-glucosidase inhibitors, derived from medicinal plants, offer a natural alternative to synthetic drugs due to their enhanced efficacy and reduced side effects. Various plant extracts, including flavonoids, alkaloids, terpenoids, and phenolics, exhibit significant alpha-glucosidase inhibitory activity. Compounds such as quercetin, berberine, curcumin, and ginsenosides have demonstrated potent anti-diabetic effects by improving insulin sensitivity, reducing oxidative stress, and modulating inflammatory pathways. The therapeutic potential of these natural inhibitors extends beyond glycemic control, offering additional cardioprotective and neuroprotective benefits. However, challenges such as variability in bioavailability, standardization, and limited clinical trials hinder their widespread adoption. Advances in formulation techniques and bioenhancers can improve their therapeutic efficacy. Future research should focus on large-scale clinical trials to validate their efficacy and optimize dosage strategies. Integrating phytoconstituent-based Alpha-glucosidase inhibitors with conventional therapies may provide a holistic approach to diabetes management. This review highlights recent advancements in identifying and characterizing plant-derived Alpha-glucosidase inhibitors, their mechanisms of action, therapeutic benefits, and challenges in clinical application. With growing interest in natural remedies, phytoconstituent-based Alpha-glucosidase inhibitors hold significant promise in developing novel antidiabetic treatments with enhanced safety and effectiveness.
Keywords: Type 2 Diabetes Mellitus; Phytoconstituents; Alpha-glucosidase inhibitors; Antidiabetic therapy; Natural compounds; Insulin resistance